2015 Science and Information Conference (SAI) 2015
DOI: 10.1109/sai.2015.7237271
|View full text |Cite
|
Sign up to set email alerts
|

Density and mobility impact on MANET routing protocols in a maritime environment

Abstract: Mobile Ad-Hoc Networks (MANETS) are multi hop wireless networks, where a packet hops through a number of intermediate nodes within coverage range of each other to reach the intended destination. The novel application of MANET routing protocols in the marine environment using available technology is one of the contributions of this work. The high cost of other available technologies which require direct connection to IP networks make our approach an attractive proposition for small craft. In this paper we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…In turn, Mobile Ad hoc NETworks (MANET) have also been explored in maritime scenarios [18,19]. Work in [18] proposed a Nautical Ad hoc NETwork (NANET) in the VHF band in order to improve the range of the individual links.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, Mobile Ad hoc NETworks (MANET) have also been explored in maritime scenarios [18,19]. Work in [18] proposed a Nautical Ad hoc NETwork (NANET) in the VHF band in order to improve the range of the individual links.…”
Section: Related Workmentioning
confidence: 99%
“…Depending on the distance of the nodes to the shore, the authors proposed to employ terrestrial nodes for enabling the communications in coastal areas and the use of P2P (ad hoc) links in further areas to the shore. From a different perspective, the authors of [19] studied the impact of typical maritime traffic patterns on the performance of different MANET routing protocols. The results showed that, in some scenarios, a boat chain can be established for transporting information from a far node to the gateway on land in a multi-hop fashion, but, in other cases, some boats are isolated with no communication capabilities.…”
Section: Related Workmentioning
confidence: 99%
“…Alternatively, Mobile Ad-hoc Networks (MANETs) have a more distributed network architecture where routing protocols do not necessarily require nodes with particular roles [122]. MANETs have already been proposed for maritime environments [109,123], but the characteristics, constraints and challenges of such environments require additional considerations such as Disruptive or Delay Tolerant Networking (DTN) and different routing protocols [113,114,116]. Table 3 presents networking options used in the literature, regarding common communication technologies, and which may be applied to various types of autonomous vehicles.…”
Section: Network and Protocolsmentioning
confidence: 99%
“…There are four foremost ad hoc routing protocols such as AODV, NMDC, TORA and destination sequence distance vector (DSDV). All these protocols are continually being enriched by the research community [10].As a result; a inclusive presentation calculation of ad hoc overwhelming protocols is required. This paper compares the performance of three ad hoc routing protocols namely, AODV, TORA and NMDC routing protocols using the Simulator Network version 2.…”
Section: Figure 1: Pattern Of Ad Hoc Networkingmentioning
confidence: 99%
“…To route the PING packet its node, needs the routing protocol. The reactive based routing protocol can be considered at the rout on demand at the start of the communication network [10]. In AODV, its considered at the normalization of control overhead.…”
Section: Efficient Network Based On Broadcasting Networkmentioning
confidence: 99%